Mental health problems of children and adolescents, with and without migration background, living in Vienna, Austria - Maria Teresa Gutmann; Metin Aysel; Zeliha Özlü-Erkilic; Christian Popow; Türkan Akkaya-Kalayci (BMC, 2019)
Abstract Background Compared to their indigenous peers, migrant children and adolescents are at increased risk for mental health problems. The aim of our study was to compare psychological disorders of children and adolescents with Turkish migration background and their native Austrian peers. Methods We analysed 302 children and adolescents aged between 7 and 18 years. The sample consisted of 100 Austrian and 100 Turkish outpatients with mental health problems, and 102 healthy controls, 52 with Austrian and 50 with Turkish background, recruited from various Viennese local child and youth centres. Results Native patients had more frequently externalizing problems (42.1%) compared to the Turkish-speaking sample (28%). However, in the control group, Turkish-speaking children and adolescents had higher levels of internalizing, depressive and anxiety symptoms compared to their native peers. Conclusions We found noticeable differences in psychological problems among children and adolescents with and without migration background. We assume that migration-related stress factors are responsible for these differences. Also, children and adolescents with migration background seek for psychological help less frequently than their indigenous peers.